النظام القانوني لرخصة التجزئة في التشريع الجزائري - رزوق, فاطمة (جامعة الوادي -University eloued, 2021)
و أخيرا نخلص أن قواعد التهيئة والتعمير بما فيها رخصة التجزئة ،هي آليات قانونية تضمن من خلالها الدولة المحافظة على الطابع العمراني الذي يمثل في الوقت الحالي أهم سمات الحضارة و الرقيFinally, we conclude that the rules of preparation and reconstruction, including the retail license, are legal mechanisms through which the state guarantees the preservation of the urban character, which at the present time represents the most important features of civilization and sophistication.
قانون عقاري
Keywords: النظام القانوني ، لرخصة التجزئة ، التشريع الجزائري; Legal system, retail license, Algerian legislation